Natural predators - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Edouard Mvogo Balla Ngono of CODASC, M Balmayo in Cameroon, tells of a nifty little rat trap designed by local children using empty tins. 'They put some grain or a nut inside the tin. They fit a lid to the tin with a piece of rubber to pull it down...